Phenotyping congestion in acute heart failure by renal flow and right heart to pulmonary circulation coupling - Alessandro Vella; Valentina Labate; Gianmarco Carenini; Eleonora Alfonzetti; Valentina Milani; Francesco Bandera; Omar Oliva; Marco Guazzi (ESC Heart Failure, 2023)
Abstract Aims In acute heart failure (AHF), kidney congestion is basic to treatment and prognosis. Its aetiology is manifold and quite unexplored in details mainly regarding the right heart to pulmonary circulation (Pc) coupling. We investigated the right heart to kidney interrelationship by Doppler renal flow pattern, right atrial dynamics, and right ventricular (RV) function to Pc coupling in AHF. Methods and results In 119 AHF patients, echocardiographic and renal Doppler data were analysed. Univariate and multivariate regression models were performed to define the determinants of a quantitative parameter of renal congestion, the renal venous stasis index (RVSI). When grouped according to different intra‐renal venous flow patterns, no differences were observed in haemodynamics and baseline renal function. Nonetheless, patients with renal Doppler evidence of congestion showed a reduced RV function [tricuspid annular plane systolic excursion (TAPSE), S′‐wave velocity, and fractional area change], impaired RV to Pc coupling [TAPSE/pulmonary artery systolic pressure (PASP) ratio], and right atrial peak longitudinal strain (RAPLS), along with signs of volume overload [increased inferior vena cava (IVC) diameters and estimated right atrial pressure]. Univariate and multivariate regression analyses confirmed TAPSE/PASP, RAPLS, and IVC diameter as independent determinants of the RVSI. RVSI was the only variable predicting the composite outcome (cardiac death, heart failure hospitalization, and haemodialysis). An easy‐to‐use echo‐derived right heart score of four variables provided good accuracy in identifying kidney congestion. Conclusions In AHF, the renal venous flow pattern combined with a right heart study phenotypes congestion and clinical evolution. Keys to renal flow disruption are an impaired right atrial dynamics and RV–Pc uncoupling. Integration of four right heart echocardiographic variables may be an effective tool for scoring the renal congestive phenotype in AHF.